2017
DOI: 10.1111/ans.14325
|View full text |Cite
|
Sign up to set email alerts
|

Gait speed predicts post‐operative medical complications in elderly gastric cancer patients undergoing gastrectomy

Abstract: Slow gait speed is an independent predictor of post-operative medical complications in elderly patients undergoing curative gastrectomy. Those patients should be managed with appropriate perioperative nutritional support and physical exercise which can improve gait speed and reduce the risk of post-operative medical complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“… 3 Meanwhile, in a study on cardiac surgery, Chung et al found that handgrip strength was a predictive factor of postoperative complications in patients with heart failure, 36 and another study reported that walking speed was a predictor of postoperative morbidities in older patients undergoing gastrectomy. 37 However, the authors only chose one component and did not compare other components in Fried’s criteria.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Meanwhile, in a study on cardiac surgery, Chung et al found that handgrip strength was a predictive factor of postoperative complications in patients with heart failure, 36 and another study reported that walking speed was a predictor of postoperative morbidities in older patients undergoing gastrectomy. 37 However, the authors only chose one component and did not compare other components in Fried’s criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Gait speed <0.2 m/s is the cut off point for extreme frailty. A slow gait speed was an independent predictor of post-operative morbidity in older patients undergoing various abdominal operations due to cancer [20,21].…”
Section: Objective Toolsmentioning
confidence: 94%
“…Six CPET-studies reported on at least two CPET variables and postoperative complications. West et al [29] found significant In the non-CPET studies, gait speed and hand grip strength were the most frequently reported tests [16,17,23]. In the study by Karlsson et al [17], a unit increase in maximal gait speed was associated with less overall complications in multivariable analysis (OR 0.29, 95% CI 0.13e0.63) whereas habitual gait speed was not.…”
Section: Overall Complicationsmentioning
confidence: 96%
“…Twelve studies analyzed preoperative physical assessment methods other than CPET [14e19, 23,27,30e34]. The TUG test was the sole focus of six studies [27,30e34], one study considered ISWT [19], three studies focused on two different physical tests (TUG and hand grip strength [15], TUG and gait speed [16] or gait speed and hand grip strength [23]), one study assessed TUG, hand grip strength and chair rise time over 10 repetitions [14], and one study reported on four physical assessment methods (hand grip strength, gait speed, number of chair stands over 30 s (chair stand test), and the 6MWT) [17,18]. Physical tests were not directly compared with each other within the individual studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation